ANALISIS STRATEGI BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI DISTRIBUTION OUTLET MAILBOX, YOGYAKARTA - Aunul Khaq Syaifti Arfiyandi; Fitroh Adhilla (Universitas Ahmad Dahlan, 2011)
This study aims to determine whether there is influence simultaneously and partial factor product, price, promotion and location of the purchasing decisions of consumers in the Distribution Outlet Mailbox in Yogyakarta and the factor of whether the greatest effect on consumer purchase decisions. The analysis used in this study is the analysis of t test (partial), f test analysis (simultaneously) and test the coefficient of multiple determination (R2). Samples taken in this study of 100 respondents who considered sufficiently representative of the population studied. Sampling technique using the incidental sampling (sampling with respondents met by chance at the time of the study). While data collecting technique using a questionnaire that is a list of questions given to a number of respondents to obtain data required in the research.Based on the results of t test analysis (partially) by Level of Significant (05) that there is influence of the partial product variable (X1) of (0,024), Price (X2) equal to (0.325), Promotion (X3) (0,000), and Location (X4) of (0.028) of the Consumer Buying Decision (Y). And based on results of test analysis f (simultaneously) is (0.000) with Level of Significant (05) and stated there is the influence of variables simultaneously Products (X1), Promotion (X3), and Location (X4) of the Consumer Buying Decision (Y) and variable rates (X2) has no effect signifika partially towards Consumer Purchase Decision (Y). The most dominant factor of influence on consumer purchasing decisions based on the data if the beta coefficient of the variable product (X1) of (0.222), Price (X2) equal to (0,110), Promotion (X3) (0.449), and Location (X4) for (0.201), factors that contribute the greatest value is a factor Promotions (X3), amounted to (0.449). The results obtained from the regression R 2 (coefficient of determination or R Square) of 0.623 means that the dependent variable (Y) in the model: Consumer Buying Decision (Y) explained by independent variables (X), namely Products (X1), Price (X2), Campaign (X3), and Location (X4) of 62.3%, while the remaining amount of 37.7% explained by other variables outside the model.